Implementation of a new parcellation of the orbitofrontal cortex in the automated anatomical labeling atlas - Rolls, Edmund T.; Joliot, Marc; Tzourio-Mazoyer, Nathalie (NeuroImage (Orlando, Fla.), 2015)
An alternative parcellation of the orbitofrontal cortex is described for the automated anatomical labeling atlas of Tzourio-Mazoyer et al. (2002) (Automated anatomical labeling of activations in SPM using a macroscopic anatomical parcellation of the MNI MRI single-subject brain. NeuroImage 15:273–289). The new parcellation of the orbitofrontal cortex follows the description provided by Chiavaras, Petrides, and colleagues (2000, 2001). The new atlas is available as a toolbox for SPM at http://www.gin.cnrs.fr/AAL2. •A new parcellation of the orbitofrontal cortex for the AAL•The AAL is the automated anatomical labeling atlas of Tzourio-Mazoyer et al. (2002).•The new atlas, AAL2, is available as aal2.nii.gz at http://www.gin.cnrs.fr.